Consciousness Energy Healing Treatment: Impact on Physicochemical and Thermal Properties of Silver Sulfadiazine - Nayak Gopal; Kumar Trivedi Mahendra; Branton Alice; Trivedi Dahryn; Jana Snehasis (Journal of Advanced Pharmaceutical Science And Technology, 2018)
Silver sulfadiazine is a topical medicine that belongs to sulfa antibiotics class of drugs and used in treating wound infections in burn patients. The aim of this study was to determine the effect of Consciousness Energy Healing Treatment (the Trivedi Effect®) on the various properties of silver sulfadiazine with the help of modern analytical techniques. The sample was divided into two parts; the first part was not given any treatment and considered as a control sample, while the second part was provided the Consciousness Energy Healing Treatment by the Biofield Energy Healer, Gopal Nayak remotely, named as the treated sample. The powder XRD data showed significant alterations in the peak intensities of the treated sample ranging from-30.71% to 47.54% compared to the control sample. The crystallite size was altered ranging from -78.12% to 1.47%; and the average crystallite size was significantly reduced by 31.62% in the treated sample compared to the control sample. The particle sizes were decreased in the treated sample by 12.75%(d10), 4.98%(d50), 0.89%(d90), and 2.92%D(4,3); thus, the specific surface area was significantly increased by 17.31% compared with the control sample. The latent heat of fusion and latent heat of decomposition were profoundly increased by 24.62% and 156.28%, respectively in the treated sample compared to the control sample. The total weight loss was increased by 3.08% and the residue amount was reduced by 4.44% in the treated sample compared to the control sample. Thus, the Trivedi Effect®-Consciousness Energy Healing Treated sample might form a new polymorph of silver sulfadiazine that possesses reduced particle size and improved thermal properties compared to the untreated sample. Therefore, the Biofield Energy treated sample can be used in nutraceutical/pharmaceutical formulation, which would show a better bioavailability and therapeutic response against various infections in comparison to the control sample.
Keywords: Silver sulfadiazine